ERA OF SUSTAINABILITY: DO THE ECONOMIC, SOCIAL, AND ENVIRONMENTAL ASPECTS HAVE A POSITIVE IMPACT ON COMMUNITY-BASED ECOTOURISM? - Septiani, Delina Herdian; Rahmani, Hani Fitria; Sriwijayanti, Irma; Pratiwi, Ratih (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2025)
Indonesia's tourism industry is undergoing a shift toward nature-based and sustainable tourism, creating opportunities for the development of community-based ecotourism. This study aims to analyze the economic, social, and environmental impacts of ecotourism development in AEWO Mulyaharja, Bogor City. A quantitative descriptive approach was used, with purposive sampling involving local communities, tourism managers, business owners, tourists, and government representatives. Data were collected through questionnaires and structured interviews and analyzed using statistical tests in SPSS. The results indicate that stakeholder perceptions of the ecotourism impact fall into the "good" category across all aspects: economic (average score 4.13), social (4.15), and environmental (4.03). A strong correlation was found between tourism managers and tourists (r = 0.806), and between business owners and tourists (r = 0.954), emphasizing the importance of collaboration among local actors. However, the government’s role showed a weak correlation with other stakeholders, highlighting the need for more strategic involvement. Although the environmental aspect was generally perceived positively, the use of renewable energy scored lower, suggesting an area for improvement. This study recommends strengthening stakeholder collaboration as a key strategy to ensure the sustainability of community-